2019
DOI: 10.1177/0954411919889194
|View full text |Cite
|
Sign up to set email alerts
|

Shear stiffness in the lower cervical spine: Effect of sequential posterior element injury

Abstract: The aim of this study was to determine the effect of the posterior ligaments and facet joints on the shear stiffness of lower cervical functional spinal units in anterior, posterior, and lateral shear. Five functional spinal units were loaded in anterior, posterior, and right lateral shear up to 100 N using a custom-designed apparatus in a materials testing machine. Specimens were tested in three conditions: intact, with the posterior ligaments severed, and with the facet joints removed. There was a significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Our findings add to this by providing clear evidence that the facets contribute a significant effect to the load response of the human thoracic spine in pure anterior shear. Additional studies on the cervical and lumbar spine add supporting evidence to the role of the facet joints in spine stability and flexibility, such as work done by Dowling‐Medley, Whyte, Howarth, Panjabi, Adams, Miller, and Quarrington 8–11,14,15,20 …”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Our findings add to this by providing clear evidence that the facets contribute a significant effect to the load response of the human thoracic spine in pure anterior shear. Additional studies on the cervical and lumbar spine add supporting evidence to the role of the facet joints in spine stability and flexibility, such as work done by Dowling‐Medley, Whyte, Howarth, Panjabi, Adams, Miller, and Quarrington 8–11,14,15,20 …”
Section: Discussionmentioning
confidence: 95%
“…Dowling-Medley et al described the stiffness of the cervical spine under anterior-posterior (A-P) shear, and Whyte and colleagues conducted multi-planar shear loading experiments in the cervical spine. 8,9 Howarth et al described the role of the facet joints under shear in a porcine cervical spine model. 10 Another study by Panjabi et al examined translation and rotation of the cervical spine in six directions, including shear.…”
Section: Kouwenhoven Et Al Performed a Biomechanical Study Of Human Andmentioning
confidence: 99%
See 1 more Smart Citation
“…The segmental masses were computed using a scaling function for the 5th, 50th, and 95th percentile implemented in the AnyBody Standing Model (AMMR v. 2.2.3). The axial and shear stiffness were adapted from previous studies ( Yoganandan et al, 2001 ; Dowling-Medley et al, 2020 ), which were varied as 0.5, 1, and 1.5 of the disc stiffness. For quasi-static inverse analysis, simple muscles were considered with three specific muscle strengths of 30, 60, and 90 N/cm 2 , whereas these values were within the normal range as published in previous literature ( Ikai and Fukunaga, 1968 ; Maganaris et al, 2001 ).…”
Section: Methodsmentioning
confidence: 99%
“…The disc stiffness plays a vital role in flexibility and load-bearing mechanism. Previously, in vitro studies showed a large variation in cervical disc axial and shear stiffness ( Moroney et al, 1988 ; Yoganandan et al, 2001 ; Dowling-Medley et al, 2020 ). These differences may influence the local kinematics, the initial contact mechanics between the facet joints ( Yoganandan et al, 2003 ; Jaumard et al, 2011 ), and the cervical spine’s overall motion and load sharing mechanism ( Cripton, 1999 ; Patwardhan et al, 2000 ).…”
Section: Introductionmentioning
confidence: 99%